Nijmegen-Breakage Syndrome; Two Siblings Presenting with Different Phenotypes - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; ELÇİOĞLU, HURİYE NURSEL; ÖĞÜLÜR, İSMAİL; BARIŞ, SAFA (BILIMSEL TIP YAYINEVI, 2016)
The Nijmegen Breakage syndrome (NBS) is characterized by chromosomal instability, combined immunodeficiency, and distinctive physical features. We present two siblings with NBS presenting with strikingly different manifestations. The proband is a 6-year-old female with short stature, microcephaly, hepatosplenomegaly, rectovaginal fistula, anal atresia, an ectopic kidney, recurrent fevers and otitis media. A 7-year-old brother has developmental delay, failure to thrive, and microcephaly without recurring infections. Both patients have hypogammaglobulinemia, B cell lymphopenia and reduced phytohaemagglutinin-induced lymphocyte proliferation. Both siblings are homozygous for the c.657_661delACAAA (p.Lys219Asnfs*16) mutation in the NBN (NBS1) gene.
Keywords: Nijmegen breakage syndrome; lymphopenia; chromosomal instability; microcephaly; pachygyria; SYNDROME GENE NBS1; 657DEL5 MUTATION